Strategies for metabolic flux analysis in plants using isotope labelling. - Roscher, A; Kruger, N; Ratcliffe, R (Elsevier, 2000)
Flux measurements through metabolic pathways generate insights into the integration of metabolism, and there is increasing interest in using such measurements to quantify the metabolic effects of mutation and genetic manipulation. Isotope labelling provides a powerful approach for measuring metabolic fluxes, and it gives rise to several distinct methods based on either dynamic or steady-state experiments. We discuss the application of these methods to photosynthetic and non-photosynthetic plant tissues, and we illustrate the different approaches with an analysis of the pathways interconverting hexose phosphates and triose phosphates. The complicating effects of the pentose phosphate pathway and the problems arising from the extensive compartmentation of plant cell metabolism are considered. The non-trivial nature of the analysis is emphasised by reference to invalid deductions in earlier work. It is concluded that steady-state isotopic labelling experiments can provide important information on the fluxes through primary metabolism in plants, and that the combination of stable isotope labelling with detection by nuclear magnetic resonance is particularly informative.